Lemah Ekonomi Antara Takdir dan Struktur Sosial (Suatu Kajian Tafsir Tematik) - Ikma Pradesta Putra Prayitna (Jurnal test, 2023)
This research aims to explain the issue of economic weakness from the perspective of al-Qur'anic tafsir by presenting the interpretations of scholars, and provide perspectives on economic empowerment by Islam and the government. The background of this topic is the increasing poverty rate in Indonesia with data from the Central Statistics Agency that in December 2022 increased by 9.57 percent. The economic weakness is divided into two, namely natural and structural. The research method used is descriptive qualitative with thematic interpretation analysis. The results of this study show that the Qur'an is concerned about the economically weak through Zakat, while the government has implemented various support programs for the poor, such as the National Safety Net (JPS), low-interest loans, and others. Weak economic conditions can occur naturally with weak natural resources and physical deficiencies. Structurally, economic weakness is caused by imbalance of power, unavailability of jobs, low education, and abuse of power. The Qur'an provides a solution so that the economy must rotate to all levels of society, it should not rotate only in the environment of the rich and rulers. Suggestions for future research to be able to examine the issue of economic weakness with a broader perspective and to include other terms that lead to the issue.